Digital teleretinal screening : teleophthalmology in practice - Goldschmidt, Leonard; Cuadros, Jorge; Yogesan, Kanagasingam (Springer Berlin Heidelberg, 2012)
With increasing population numbers and a limited supply of ophthalmologists, new ways are being found to perform eye screening. Digital retinal imaging carried out by primary care providers and nurses, followed by remote image interpretation (teleretinal imaging), is rapidly acquiring a crucial role. A number of successful digital teleretinal screening programs have now been established on different continents, permitting the detection of major diseases such as diabetic retinopathy and glaucoma in patients who would otherwise have been beyond the reach of a trained ophthalmologist.   In this book, experts from around the world describe how digital teleretinal screening can be set up and optimally utilized. Technical issues are discussed, and the appropriate use of screening for different diseases and in different age groups is explained. The major part of the book draws upon the clinical experience of leading practitioners in a wide range of teleretinal applications. The aim is to provide high-quality information for clinicians and other health professionals who are involved in eye care delivery, so that they can assess how teleretinal screening might be applied to their working practice.